Development of mobile application for transmission line and plane wave analysis - Tan, Wei Teck (Nanyang Technological University, 2024)
The studies on Electromagnetics in the course of Electrical Electronic Engineering (EEE) is crucial and fundamental for engineers to comprehend and innovate in the modern technological field. With the need to strengthen the foundation, this project is aimed to enhance the learning and importance of understanding the electromagnetic principles in this field through the interface of a mobile application. The development of the mobile application will include the use of Google Limited Liability Company (LLC)’s Flutter Software Development Kit (SDK) and Dart programming language. This application is design for students learning the analysis of plane waves and transmission line in the course of study EE3001 Electromagnetism, using the availability of the Dart packages and widgets in the Flutter SDK. This serves as a tool for students when they are solving the tutorial questions covered in the module, and the application can display the detailed working steps to allow the students to understand how the answers are being derived.